Stabilization of tie-line power flow by robust SMES controller for interconnected power system with wind farms - Dechanupaprittha, Sanchai; Hongesombut, Komsan; Watanabe, Masayuki; Mitani, Yasunori; Ngamroo, Issarachai (My University, 2007)
This paper presents the use of superconducting magnetic energy storage (SMES) with robust controllers for stabilization of tie-line power flow in a longitudinally interconnected power system with wind farms. The high penetration of wind power with abrupt changes causes fluctuations of tie-line power flow and significantly affects the effective use of transmission lines. A simultaneous active and reactive power control scheme of SMES including a characteristic of SMES coil current is employed for realizing a permissible range of SMES operation. Moreover, a multiplicative uncertainty model is considered in the parameter optimization of robust SMES controllers by using a heuristic method. Finally, simulation results are carried out to show the effectiveness and robustness under various situations. © 2007 IEEE.
Keywords: Power system stabilization; Robust control; Superconducting magnetic energy storage; Wind farms